Establishing a Hematopoietic Stem Cell Transplantation Unit A Practical Guide (Springer International Publishing, 2018)
This text aims to provide simplified practical guidelines to start a hematopoietic stem cell transplantation unit which could be implemented in most centers and countries worldwide. The book also provides guidelines for existing transplantation units to upgrade their practice and implement new policies and procedures, in addition to developing therapies according to latest international standards and regulations. The book covers a wide range of practical implementation tools including HSCT program team structure, building inpatient and outpatient HSCT units, requisite laboratory support for transplantation program, practical aspects of stem cell collection and processing, HSCT program quality management, education and training, and data management. The book also addresses cost effectiveness and recommendations for establishing transplantation program in countries with limited resources. Written by group of internationally established experts in their corresponding hematopoietic stem cell transplantation fields, with contributions from many leaders of hematopoietic stem cell transplantation organizations, Establishing a Hematopoietic Stem Cell Transplantation Unit: A Practical Guide is an essential, practical resource for all members of the multidisciplinary hematopoietic stem cell transplantation team.